Taxonomical classification of barriers for scaling agile methods in global software development environment using fuzzy analytic hierarchy process - Shameem, Mohammad; Kumar, Rakesh Ranjan; Nadeem, Mohammad; Khan, Arif Ali (Applied soft computing, 2020)
Increasingly, software development organizations are scaling agile practices in the global software development (GSD) environment in order to meet the requirements of the quickly changing and regularly developing business environment. The main objectives of this study are to investigate the key barriers and develop a prioritization-based taxonomy of the barriers for scaling agile development in the GSD environment. Total twenty-two barriers were extracted from the available literature and categorized into five categories, i.e. “human resources management”, ‘coordination”, “technology”, “project management”, and “software methodology”. In the next phase, the identified barriers and their categories were further validated using the questionnaire survey. In the final phase, fuzzy-AHP method, a multi-criterion decision making (MCDM) technique, was applied to prioritize and taxonomy of identified barriers and their related categories was designed. The contribution of this study is not limited to investigate the barriers, but it also provides the roadmap to tackle the issues related to the scaling agile methods in the GSD environment. •Identifying the barriers which negatively impact on the scaling programs of agile development in GSD environment.•Categorizing the identified barriers according to their types.•Validation of the identified barriers using the questionnaire survey.•Prioritizing the barriers using fuzzy AHP method by collecting responses of pair-wise comparison of factors.